Social Media as a Digital Marketing Tool for Agricultural Products - Kusuma, Marsliana Indah; Lutfiani, Nanda Wanifa; Khamdi, Ali (Economics and Business International Conference Proceeding, 2024)
allows people to interact with each other, exchange information and even as a medium to promote a product or service through the internet. Social media has become an integral part of everyday life. The rapid development of technology has a major impact on the increasing use of social media. Social media is not only used to find information, communicate and socialize but also used to market a product. Social media as a means of marketing agricultural products is very important in this digital era, because in addition to being able to access a wider market, the use of social media as a marketing tool can also increase producer profits. This research uses a bibliometric analysis approach to describe the role of social media as a digital marketing tool applied to agricultural products. The practice of e-commerce and e-business turns out to have many advantages for both companies and consumers, the purpose of this study is to determine the existence of advertising, marketing and sales programs and other benefits in marketing and selling agricultural products through social media and their influence on purchasing decisions for products sold in online stores and social media in order to support producer profitability.